Guideline for diagnosis and treatment of subacromial pain syndrome: A multidisciplinary review by the Dutch Orthopaedic Association - Diercks, Ron; Bron, Carel; Dorrestijn, Oscar; Meskers, Carel; Naber, René; de Ruiter, Tjerk; Willems, Jaap; Winters, Jan; van der Woude, Henk Jan (Acta orthopaedica, 2014)
Treatment of "subacromial impingement syndrome" of the shoulder has changed drastically in the past decade. The anatomical explanation as "impingement" of the rotator cuff is not sufficient to cover the pathology. "Subacromial pain syndrome", SAPS, describes the condition better. A working group formed from a number of Dutch specialist societies, joined by the Dutch Orthopedic Association, has produced a guideline based on the available scientific evidence. This resulted in a new outlook for the treatment of subacromial pain syndrome. The important conclusions and advice from this work are as follows: (1) The diagnosis SAPS can only be made using a combination of clinical tests. (2) SAPS should preferably be treated non-operatively. (3) Acute pain should be treated with analgetics if necessary. (4) Subacromial injection with corticosteroids is indicated for persistent or recurrent symptoms. (5) Diagnostic imaging is useful after 6 weeks of symptoms. Ultrasound examination is the recommended imaging, to exclude a rotator cuff rupture. (6) Occupational interventions are useful when complaints persist for longer than 6 weeks. (7) Exercise therapy should be specific and should be of low intensity and high frequency, combining eccentric training, attention to relaxation and posture, and treatment of myofascial trigger points (including stretching of the muscles) may be considered. (8) Strict immobilization and mobilization techniques are not recommended. (9) Tendinosis calcarea can be treated by shockwave (ESWT) or needling under ultrasound guidance (barbotage). (10) Rehabilitation in a specialized unit can be considered in chronic, treatment resistant SAPS, with pain perpetuating behavior. (11) There is no convincing evidence that surgical treatment for SAPS is more effective than conservature management. (12) There is no indication for the surgical treatment of asymptomatic rotator cuff tears.